Non-native english speaking elementary ell teachers’ culturally responsive leadership profile in an ESL context - Ekiaka Nzai, Valentin; Gómez, Patricia; Reyna, Concepción; Jen, Kang-Fan (Colombian Applied Linguistics Journal, 2012)
Culturally responsive instruction has been suggested as quality education (Edwards, 2003) for minority students in subtractive and additive bilingualism settings. However, analytical curriculum development of several official English programs revealed that the gender-centric (malecentric) and Ethno-centric (Euro/Western-centric) approaches were deeply embedded in most English textbooks of curriculum development. The intent of partial mixed methods paper consisted of exploring some non-native English speaking teachers English teachers’ culturally responsive leadership profile in order to further the discussion on not only how to promote English curriculum transformation in English as second language (ESL) and English as foreign language (EFL) settings, but also to effectively train culturally responsive non-native English speaking (NNES) English pre-service teachers. Comparative data analysis suggested that there were no causal relationship between NNES English teachers’ culturally responsive leadership styles and their abilities to perform multicultural transformation of English curriculums. To be highly effective in transforming English curriculum, NNES English teachers needed to be systematically trained on how to do so. Implications for NNES English pre-service teacher education are framed from the culturally responsive and anti-oppressive education approaches.